EFEKTIVITAS SISTEM PENGENDALIAN MANAJEMEN ATAS PENDAPATAN TERHADAP TINGKAT LABA PADA PT.XYZ - Karaniya, Karaniya; Rasyid, Rosmita (Fakultas Ekonomi, Universitas Tarumanagara, 2024)
This research was conducted at PT. XYZ which is a construction equipment supplier company, with the aim of knowing the management control system for income that is applied to PT. XYZ and how it affects the company's profit and how the level of effectiveness of the management control system. The type of research used is descriptive research with data collection methods through interviews with managers from PT.XYZ. Methods of data processing using qualitative analysis methods. The results of this study indicate that the control system at PT. XYZ is still ineffective due to management neglect and employee failure in carrying out orders from managers and the system that has been made is not fully implemented with discipline by PT. XYZ employees.